2019
DOI: 10.7717/peerj.6971
|View full text |Cite
|
Sign up to set email alerts
|

EngineeringEscherichia colifor the production of butyl octanoate from endogenous octanoyl-CoA

Abstract: Medium chain esters produced from fruits and flowering plants have a number of commercial applications including use as flavour and fragrance ingredients, biofuels, and in pharmaceutical formulations. These esters are typically made via the activity of an alcohol acyl transferase (AAT) enzyme which catalyses the condensation of an alcohol and an acyl-CoA. Developing a microbial platform for medium chain ester production using AAT activity presents several obstacles, including the low product specificity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 95 publications
(143 reference statements)
0
6
0
Order By: Relevance
“…AATs have also been known to contribute to ester biosynthesis in various microorganisms, for instance, Saccharomyces cerevisiae (Kruis et al 2018 ; Saerens et al 2010 ), Yarrowia lipolytica (Gao et al 2018 ; Yu et al 2020 ), C . acetobutylicum (Noh et al 2018 ), and E. coli (Chacon et al 2019 ). Another contribution of AAT on esters synthesis, particularly in E. coli , has been demonstrated by chloramphenicol O -acetyltransferases (CATs, EC 2.3.1.28), an AAT homolog isolated from Streptococcus aureus (Alonso-Gutierrez et al 2013 ; Rodriguez et al 2014 ).…”
Section: Production Of Bb By Engineered E Coli Wit...mentioning
confidence: 99%
“…AATs have also been known to contribute to ester biosynthesis in various microorganisms, for instance, Saccharomyces cerevisiae (Kruis et al 2018 ; Saerens et al 2010 ), Yarrowia lipolytica (Gao et al 2018 ; Yu et al 2020 ), C . acetobutylicum (Noh et al 2018 ), and E. coli (Chacon et al 2019 ). Another contribution of AAT on esters synthesis, particularly in E. coli , has been demonstrated by chloramphenicol O -acetyltransferases (CATs, EC 2.3.1.28), an AAT homolog isolated from Streptococcus aureus (Alonso-Gutierrez et al 2013 ; Rodriguez et al 2014 ).…”
Section: Production Of Bb By Engineered E Coli Wit...mentioning
confidence: 99%
“…21 Analogous studies have also described how the selection of the mutation site was driven by its proximity to the conserved HHXXXDG motif of wax ester synthases, and how altering its surrounding could modify the enzyme substrate affinity. 22,23…”
Section: Introductionmentioning
confidence: 99%
“…Bioprospecting and protein engineering are promising strategies to find novel AATs with high specificity and activity towards a target ester. For instance, AAT of Actinidia chinensis (AAT Ac ) was engineered to create a AAT Ac S99G variant that enhanced n ‐butyl octanoate production in Escherichia coli about 4.5‐fold higher than the wildtype (Chacon et al, 2019). Similarly, Seo et al reported that a single F97W mutation in CAT of the mesophilic Staphylococcus aureus (CAT Sa ), identified by a model‐guided protein design, achieved ~3.5‐fold increase in isobutyl acetate (IBA) production in a thermophilic, cellulolytic bacterium Clostridium thermocellum (Seo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%